Frontières entre récit et hors récit dans les œuvres narratives de Lope de Vega - Florence Raynié (Les Cahiers de Framespa)
Taking as our corpus the narrative fiction of Lope de Vega, the present study demonstrates how the separation between the story and the micro-structures that interrupt it takes place, and identifies the formal and semantic textual markers that constitute the border between the micro-structures and the text as a whole. Using an approach that is more theoretical than analytical, we attempt to state the criteria for determining the border between the macro-narrative structure of the story and the micro-structures that disturb it. Therefore, we view the question of «micro-narratives and borders» within a larger perspective by placing the micro-narratives within the ensemble of micro-structures that interrupt the narrative continuum.